Swear Words Types Utilization in Traumazine Album Song Lyrics by Megan Thee Stallion - Bobby Samuel Pandiangan; Lerissa Daniela (Universitas Dian Nuswantoro, 2023)
The study of word meaning is formulated in semantics. Language as a medium of communication constructs meaning and structure. Communication can be done through many mediums and one of them is song lyrics. Song has its own uniqueness in choosing words, suit to the genre. In the modern era, the young generation tempts to consume a lot more media and is impacted by them then utilize it as a normal in daily communication. Therefore, this research made to analyze the utilization of swear words in rap song lyrics by classifying the types using the theory of Chirico 2014. This research uses the qualitative descriptive method. The data is collected from the eighteen song lyrics in the Traumazine album by Megan Thee Stallion. Data is analyzed with the theory of swear words by Chirico 2014, furthermore defines the meaning using the Cambridge dictionary as a primary and the Urban dictionary as the secondary dictionary. As a result, all four types of swear words which are cursing, profanity, vulgarity, and obscenity exist in the album. There is a new phenomenon as well, where the researcher found that the repetition of swear words is commonly used in rap songs. Moreover, bitch used to represent a female and nigga to represent a male repeatedly found among the 18 songs.